Կարմելյանների գործունեությունը Սեֆյան շահեր Աբբաս Երկրորդի, Սուլեյմանի և Սուլթան Հուսեյնի կառավարման տարիներին - Մարտոյան, Թեհմինե («Զանգակ - 97»)
In the article it goes about the activity of the Carmelites in the years оf reign of shahs Abbas II, Sulaiman and Sultan-Husain. Düring the reign оf shah Abbas II things were not going well for the poor Armenian and Syrian Christians, because of a new grand wazir who was a bigoted Muhammad an and antagonislic to Christianity. Religious Piter makes circumstantial statements regarding the tyrannous rule of shah Abbas II.
Keywords: Պատմություն